Quantum dot and electroluminescent device
By designing quantum dots with specific core and core-shell structures, the problem of insufficient blue-light QLED lifetime is solved and higher photoluminescence efficiency and QLED lifetime are achieved.
Patent Information
- Application Number
- CN202310897791.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
AI Technical Summary
The insufficient lifespan of Blu-ray QLED has become a bottleneck that limits the commercialization of QLEDs.
Design a quantum dot whose core material is ZnxCd1-xS. The core size is not less than 3nm. It is covered with at least one set of inner shell units and outer shell layers. The band gap of the first inner shell layer is larger than the band gap of the core. The second The band gap of the inner shell layer is smaller than the band gap of the first inner shell layer, and the band gap of the outer shell layer is greater than or equal to the band gap of the first inner shell layer.
By increasing the core size of quantum dots and optimizing the core-shell structure, the destructive effect of accumulated charge on the exciton transition of quantum dots is reduced, thereby improving the lifetime and photoluminescence efficiency of QLEDs.
Smart Images

Figure CN119342981A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of display technology, in particular to a quantum dot and an electroluminescent device. Background Art
[0002] Active quantum dot light-emitting diode display technology (AMQLED) is widely regarded as the next generation display technology because of its wide color gamut, high color purity, high brightness, low power consumption, high response speed, and flexibility.
[0003] At present, the efficiency of red, green and blue QLEDs is close to or has reached the theoretical limit; in terms of lifespan, the performance of red and green QLEDs can also fully meet the requirements of commercialization. The only bottleneck is that the lifespan of blue QLEDs is not enough. Therefore, solving the lifespan problem of blue QLEDs is of great significance to promoting the commercialization of QLEDs. Summary of the invention
[0004] Based on this, it is necessary to provide a quantum dot and an electroluminescent device to address the problem of how to improve the lifespan of blue light QLED.
[0005] A quantum dot, comprising a core, at least one group of inner shell units and an outer shell layer sequentially coated on the surface of the core;
[0006] The material of the core is Zn x Cd 1-x S, wherein x is 0 to 1; the size of the core is not less than 3 nm;
[0007] Each group of the inner shell units comprises a first inner shell and a second inner shell in a direction away from the inner core, wherein the band gap of the first inner shell is larger than the band gap of the inner core and the band gap of the second inner shell;
[0008] The band gap of the outer shell layer is greater than or equal to the band gap of the first inner shell layer.
[0009] The quantum dots using the technical solution of the present invention have a relatively large core size, which can reduce the destructive effect of accumulated charge on the exciton transition of the quantum dots when the QLED charge accumulates, thereby maintaining a high photoluminescence quantum yield for a longer time, which helps to improve the life of the QLED; the band gap of the first inner shell layer is larger than the band gap of the inner core, which can effectively confine electrons or holes on the surface of the inner core, so that the quantum dots of the present invention have a high photoluminescence quantum yield; the band gap of the first inner shell layer is larger than the band gap of the second inner shell layer, which can make the charge carriers enter the quantum dots more effectively through the tunneling process, thereby improving the charge balance level of the QLED, which helps to obtain a high device efficiency; the band gap of the outer shell layer is the widest, which can make the quantum dots have a high photoluminescence quantum yield and stability, further improving the life of the QLED. Therefore, the present invention achieves that the photoluminescence characteristics of the quantum dots are more resistant to the destructive effects of accumulated charges through the design of the size of the quantum dots and the core-shell structure, thereby making the QLED have a longer life.
[0010] In a feasible implementation, the size of the core is 3nm to 15nm; and / or
[0011] The size of the quantum dots is 10 nm to 30 nm; and / or
[0012] The thickness of the first inner shell layer, the second inner shell layer and the outer shell layer are all 0.35 nm to 3.5 nm.
[0013] In a feasible implementation, the material of the core is Zn x Cd 1-x S, where x is 0.2 to 0.7.
[0014] In a feasible implementation, the material of the core is Zn x Cd 1-x S, where x is 0.4 to 0.6.
[0015] In a feasible implementation, the material of the first inner shell layer is selected from Zn y Cd 1-y At least one of S and ZnSeS, wherein y is x-1, and x<y<1;
[0016] The material of the second inner shell layer is selected from Zn z Cd 1-z At least one of S, ZnCdSe and ZnCdSeS, wherein z<y;
[0017] The material of the outer shell layer is selected from at least one of ZnCdS, ZnSeS and ZnS.
[0018] In a feasible implementation, the material of the second inner shell layer is Zn zCd 1-z S, where z ≥ x.
[0019] In a feasible implementation, the difference between the band gap of the first inner shell layer and the band gap of the core is 0.2eV~1eV, the difference between the band gap of the first inner shell layer and the band gap of the second inner shell layer is 0.1eV~1eV, and the difference between the band gap of the outer shell layer and the band gap of the first inner shell layer is 0.1eV~1eV.
[0020] In a feasible implementation, the number of groups of the inner shell units is one group;
[0021] Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.5 Cd 0.5 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S and ZnS;
[0022] Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.4 Cd 0.6 S, ZnSeS, ZnCdSe and ZnS;
[0023] Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.2 Cd 0.8 S, ZnSeS, ZnCdSe and ZnS;
[0024] Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.2 Cd 0.8 S, Zn 0.8 Cd 0.2 S, ZnCdSe and ZnS;
[0025] Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.6 Cd 0.4 S, ZnSeS, ZnCdSe and ZnS;
[0026] Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.7 Cd 0.3 S, ZnSeS, ZnCdSe and ZnS.
[0027] In a feasible implementation, the number of groups of the inner shell units is two, and each group of the inner shell units includes a first inner shell and a second inner shell;
[0028] Preferably, the materials of the inner core, the first inner shell layer, the second inner shell layer, the first inner shell layer, the second inner shell layer and the outer shell layer from the inner core to the outer shell layer are Zn 0.5 Cd 0.5 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S and ZnS.
[0029] An electroluminescent device comprises a quantum dot light-emitting layer, wherein the quantum dot light-emitting layer comprises any one of the above-mentioned quantum dots.
[0030] Experimental verification shows that the electroluminescent device of the present invention has high efficiency and lifespan, and is suitable for wide application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the structure of a quantum dot according to one embodiment of the present invention;
[0032] Figure 2 Schematic diagram of the band gap of quantum dots according to one embodiment of the present invention;
[0033] Figure 3 A schematic diagram of the structure of a quantum dot according to another embodiment of the present invention;
[0034] Figure 4 is a schematic structural diagram of an electroluminescent device according to one embodiment of the present invention;
[0035] Figure 5 CE-L curves of the QLEDs of Example 8 of the present invention and Comparative Example 2;
[0036] Figure 6 LT curves of the QLEDs of Example 8 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0039] According to relevant research, blue QLEDs have obvious charge accumulation problems, and the accumulated charges may exist in the hole transport layer, the light-emitting layer, or the electron transport layer. These accumulated charges will cause complex physical and chemical processes, which is a key factor causing the low life of blue light QLEDs. To this end, the present invention proposes a quantum dot and electroluminescent device that can prevent the photoluminescence quantum yield (PLQY) of quantum dots from decreasing too quickly, thereby increasing the life of blue light QLEDs.
[0040] See also Figure 1 and Figure 2 The quantum dot 100 of one embodiment of the present invention comprises a core 110, at least one group of inner shell units 120 and an outer shell 130 sequentially coated on the surface of the core 110. Specifically in this embodiment, the number of groups of the inner shell units 120 is one group.
[0041] The material of the core 110 is Zn x Cd 1-x S, where x is 0 to 1; the size of the core 110 is not less than 3 nm. Wherein, x is preferably greater than 0 and less than 1. It should be noted that the "size" in the present invention generally refers to the diameter. The size of the core 110 in the quantum dot 100 of this embodiment is relatively large, which can reduce the destructive effect of the accumulated charge on the exciton transition of the quantum dot when the QLED charge accumulates, thereby maintaining a high photoluminescence quantum yield for a longer time, which helps to improve the life of the QLED.
[0042] The inner shell unit 120 includes a first inner shell 121 and a second inner shell 122 in a direction away from the inner core 110, and the band gap of the first inner shell 121 is larger than the band gap of the inner core 110 and the band gap of the second inner shell 122. The band gap of the first inner shell 121 is larger than the band gap of the inner core 110, which can effectively confine electrons or holes on the surface of the inner core 110, and can make the quantum dot 100 of this embodiment have a high photoluminescence quantum yield, which can reach more than 80%. The band gap of the first inner shell 121 is larger than the band gap of the second inner shell 122, which can make the charge carriers enter the quantum dot 100 more effectively through the tunneling process, thereby improving the charge balance level of the QLED and helping to obtain high device efficiency.
[0043] The band gap of the outer shell layer 130 is greater than or equal to the band gap of the first inner shell layer 121. In this embodiment, the band gap of the outer shell layer 130 is greater than or equal to the band gap of the first inner shell layer 121, which can make the quantum dots have high photoluminescence quantum yield and stability, further improving the life of the QLED. Stability refers to light stability and chemical stability.
[0044] On the basis of the above-mentioned embodiment, the size of the core 110 is 3nm to 15nm. At this time, the size of the core 110 can be kept at a relatively large level, so as to reduce the destructive effect of the accumulated charge on the quantum dot exciton transition when the QLED charge accumulates, thereby maintaining a high photoluminescence quantum yield for a longer time, which helps to improve the life of the QLED; at the same time, it can also avoid the core 110 being too large to affect the demand for wavelength and the selection of the inner shell unit 120 and the outer shell 130. Further, the size of the core 110 can be, for example, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm or 15nm.
[0045] Based on the above embodiments, the size of the quantum dot 100 is 10 nm to 30 nm. The size of the quantum dot 100 is the sum of the size of the core 110, the thickness of at least one group of inner shell units 120 and the outer shell 130. At this time, the quantum dot 100 can have more stable luminous efficiency and effective charge injection capability under charge accumulation.
[0046] On the basis of the above-mentioned embodiment, the thickness of the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are all 0.35nm to 3.5nm. The first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 in the above-mentioned thickness range can repair the defects on the surface of the core 110. Further, the thickness of the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 can be, for example, 0.35nm, 0.7nm, 1.05nm, 1.4nm, 1.75nm, 2.1nm, 2.45nm, 2.8nm, 3.15nm or 3.5nm.
[0047] Based on the above-mentioned embodiment, the material of the core 110 is Zn x Cd 1-x S, wherein x is 0.2 to 0.7. At this time, the band gap of the core 110 can reasonably match the band gaps of the inner shell unit 120 and the outer shell 130, which helps to obtain high device efficiency and device life. Further, x in the material of the core 110 is 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7.
[0048] Based on the above-mentioned embodiment, the material of the core 110 is Zn x Cd 1-x S, wherein x is 0.4 to 0.6. At this time, the band gap of the core 110 is optimally matched with the band gaps of the inner shell unit 120 and the outer shell 130, which is helpful to obtain higher device efficiency and device life.
[0049] Based on the above embodiment, the material of the first inner shell layer 121 is selected from Zn y Cd 1-y At least one of S and ZnSeS, wherein y is x-1, and x<y<1; the material of the second inner shell layer 122 is selected from Zn z Cd 1-z At least one of S, ZnCdSe and ZnCdSeS, wherein z<y; the material of the outer shell 130 is selected from at least one of ZnCdS, ZnSeS and ZnS. In the quantum dot 100 of this embodiment, the lattice matching of the materials of the core 110, the first inner shell 121, the second inner shell 122 and the outer shell 130 can prevent the quantum dot 100 from collapsing.
[0050] Based on the above embodiment, the material of the second inner shell layer 122 is Zn z Cd 1-z S, where z≥x. At this time, the band gap of the second inner shell layer 122 is greater than the band gap of the inner core 110, and the second inner shell layer 122 can still play a role in limiting the excitons in the inner core, which is conducive to obtaining high luminous efficiency.
[0051] On the basis of the above-mentioned embodiment, the difference between the band gap of the first inner shell layer 121 and the band gap of the core 110 is 0.2eV to 1eV, the difference between the band gap of the first inner shell layer 121 and the band gap of the second inner shell layer 122 is 0.1eV to 1eV, and the difference between the band gap of the outer shell 130 and the band gap of the first inner shell layer 121 is 0.1eV to 1eV. At this time, the band gaps of the core 110, the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are reasonably matched, which helps to obtain higher device efficiency and device life.
[0052] Based on the aforementioned embodiment, the surface of the quantum dot 100 has a ligand, and the surface ligand of the quantum dot 100 can be an amino group, an organic phosphorus, a carboxylic acid or a thiol, etc. The surface ligand can make the quantum dot of the present invention have a high PLQY and solubility.
[0053] Based on the above embodiment, the materials of the core 110, the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are Zn 0.5 Cd 0.5 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S and ZnS. It has been verified through experiments that the quantum dot structure of this embodiment can make the electroluminescent device have high efficiency and lifespan.
[0054] Based on the above embodiment, the materials of the core 110, the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are Zn 0.4 Cd 0.6 S, ZnSeS, ZnCdSe and ZnS. It has been verified through experiments that the quantum dot structure of this embodiment can make the electroluminescent device have high efficiency and lifespan.
[0055] Based on the above embodiment, the materials of the core 110, the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are Zn 0.2 Cd 0.8 S, ZnSeS, ZnCdSe and ZnS. It has been verified through experiments that the quantum dot structure of this embodiment can make the electroluminescent device have high efficiency and lifespan.
[0056] Based on the above embodiment, the materials of the core 110, the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are Zn 0.2 Cd 0.8 S, Zn 0.8 Cd 0.2 S, ZnCdSe and ZnS. Experimental verification shows that the quantum dot structure of this embodiment can make the electroluminescent device have high efficiency and lifespan.
[0057] Based on the above embodiment, the materials of the core 110, the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are Zn 0.6 Cd 0.4 S, ZnSeS, ZnCdSe and ZnS. It has been verified through experiments that the quantum dot structure of this embodiment can make the electroluminescent device have high efficiency and lifespan.
[0058] Based on the above embodiment, the materials of the core 110, the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are Zn 0.7 Cd 0.3 S, ZnSeS, ZnCdSe and ZnS. It has been verified through experiments that the quantum dot structure of this embodiment can make the electroluminescent device have high efficiency and lifespan.
[0059] It should be noted that, in the above embodiment, the number of groups of inner shell units is one group, but in the quantum dots of the present invention, the number of groups of inner shell units is not limited thereto, and may also be two groups or more than two groups.
[0060] See also Figure 3 A quantum dot 200 according to another embodiment of the present invention includes a core 210, an inner shell unit 220 and an outer shell 230 sequentially coated on the surface of the core 210. The inner shell unit 220 includes a first inner shell 221 and a second inner shell 222 in a direction away from the core 210.
[0061] Different from the quantum dot 100 of the aforementioned embodiment, in the quantum dot 200 of this embodiment, there are two groups of inner shell units 220. It should be noted that the material selection of the first inner shell 221 and the second inner shell 222 of each group of inner shell units 220 is still in accordance with the aforementioned selection, but the thickness should be thinner, for example, the total thickness of the two groups of inner shell units 220 is the same as the total thickness of one group of inner shell units in the aforementioned embodiment.
[0062] On the basis of the above-mentioned embodiment, the materials of the inner core 210, the first inner shell 221, the second inner shell 222, the first inner shell 221, the second inner shell 222 and the outer shell 230 from the inner core 210 to the outer shell 230 are Zn in sequence. 0.5 Cd 0.5 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4S and ZnS. It has been verified through experiments that the quantum dot structure of this embodiment can make the electroluminescent device have high efficiency and lifespan.
[0063] In the quantum dot 200 of the present embodiment, the core 210 can reduce the destructive effect of the accumulated charge on the exciton transition of the quantum dot when the charge of the QLED is accumulated, so that a high photoluminescence quantum yield can be maintained for a longer time, which helps to improve the life of the QLED; the band gap of the first inner shell layer 221 is greater than the band gap of the core 210, which can effectively confine electrons or holes on the surface of the core 210, so that the quantum dot 200 of the present embodiment has a high photoluminescence quantum yield, which can reach more than 80%; and the band gap of the first inner shell layer 221 is greater than the band gap of the second inner shell layer 222, and the combination of two groups of thinner inner shell units 220 can further enable the charge carriers to enter the quantum dot 200 more effectively through the tunneling process, thereby improving the charge balance level of the QLED, which helps to obtain high device efficiency; the band gap of the outer shell layer 230 is greater than or equal to the band gap of the first inner shell layer 221, which can make the quantum dot have a high photoluminescence quantum yield and stability, and further improve the life of the QLED.
[0064] The quantum dots using the technical solution of the present invention have a relatively large core size, which can reduce the destructive effect of accumulated charge on the exciton transition of the quantum dots when the QLED charge accumulates, thereby maintaining a high photoluminescence quantum yield for a longer time, which helps to improve the life of the QLED; the band gap of the first inner shell layer is larger than the band gap of the inner core, which can effectively confine electrons or holes on the surface of the inner core, so that the quantum dots of the present invention have a high photoluminescence quantum yield; the band gap of the first inner shell layer is larger than the band gap of the second inner shell layer, which can make the charge carriers enter the quantum dots more effectively through the tunneling process, thereby improving the charge balance level of the QLED, which helps to obtain a high device efficiency; the band gap of the outer shell layer is the widest, which can make the quantum dots have a high photoluminescence quantum yield and stability, further improving the life of the QLED. Therefore, the present invention achieves that the photoluminescence characteristics of the quantum dots are more resistant to the destructive effects of accumulated charges through the design of the size of the quantum dots and the core-shell structure, thereby making the QLED have a longer life.
[0065] An electroluminescent device according to an embodiment includes a quantum dot light-emitting layer, wherein the quantum dot light-emitting layer includes any of the above-mentioned quantum dots. The electroluminescent device may be a positive-type device or a reverse-type device, which is not limited in the present invention.
[0066] See also Figure 4The electroluminescent device 300 of one embodiment includes a substrate 310, an anode 320, a hole injection layer (HIL) 330, a hole transport layer (HTL) 340, a quantum dot light emitting layer 350, an electron transport layer (ETL) 360 and a cathode 370, which are sequentially arranged. The material of the anode 320 may be, for example, ITO or IZO, the material of the hole injection layer 330 may be, for example, PEDOT:PSS, phosphomolybdic acid or phosphotungstic acid, the material of the hole transport layer 340 may be selected from at least one of TFB, PVK, Poly-TPD, NPB, CBP, TCTA and NiO, the material of the electron transport layer 360 may be, for example, ZnO, doped ZnO (the dopant includes Al, Mg, Ga, Hf, N, P, or a combination thereof) or SnO2, and the material of the cathode 370 may be, for example, Al or Ag.
[0067] Experimental verification shows that the electroluminescent device of the present invention has high efficiency and lifespan, and is suitable for wide application.
[0068] With reference to the above implementation contents, in order to make the technical solution of the present application more specific, clear and easy to understand, the technical solution of the present application is now exemplified. However, it should be noted that the contents to be protected by the present application are not limited to the following Examples 1 to 14.
[0069] Example 1
[0070] This embodiment provides a quantum dot and a method for preparing the same. The structure of the quantum dot 100 of this embodiment is as follows: Figure 1 As shown, the core 110, a group of inner shell units 120 and an outer shell 130 are sequentially coated on the surface of the core 110, and the inner shell unit 120 includes a first inner shell 121 and a second inner shell 122. The materials of the core 110, the first inner shell 121, the second inner shell 122 and the outer shell 130 are Zn 0.5 Cd 0.5 S / Zn 0.8 Cd 0.2 S / Zn 0.6 Cd 0.4 S / ZnS. The diameter of the quantum dot 100 of this embodiment is 14.6 nm, the diameter of the core 110 is 5 nm, and the thicknesses of the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are 2.1 nm, 1.5 nm and 1.2 nm respectively.
[0071] The steps for preparing the quantum dots in this embodiment are as follows:
[0072] 1) Add 4 mmol of zinc acetate, 0.6 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0073] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 25 minutes to obtain a quantum dot core solution;
[0074] 3) dissolving 0.5 mmol sulfur powder in 0.5 ml trioctylphosphine and 0.15 mmol cadmium acetate in 1.5 ml oleic acid, then mixing the two and slowly (0.07 ml / min) injecting them into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 30 minutes;
[0075] 4) dissolving 0.25 mmol sulfur powder in 0.25 ml trioctylphosphine and 0.1 mmol cadmium acetate in 1 ml oleic acid, then mixing the two and slowly (0.05 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 20 minutes;
[0076] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0077] 6) Cooling the solution in 5) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0078] Example 2
[0079] This embodiment provides a quantum dot and a preparation method thereof. The difference between the quantum dot 100 of this embodiment and the quantum dot 100 of embodiment 1 is that the materials of the core 110, the first inner shell 121, the second inner shell 122 and the outer shell 130 are Zn 0.4 Cd 0.6 S / ZnSeS / ZnCdSe / ZnS. The diameter of the quantum dot 100 of this embodiment is 14.1 nm, the diameter of the core 110 is 4.5 nm, and the thicknesses of the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are 2.1 nm, 1.5 nm and 1.2 nm respectively.
[0080] The steps for preparing the quantum dots in this embodiment are as follows:
[0081] 1) Add 3 mmol of zinc acetate, 0.7 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0082] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 20 minutes to obtain a quantum dot core solution;
[0083] 3) dissolving 0.25 mmol sulfur powder and 0.25 mmol selenium powder in 0.5 ml trioctylphosphine, and then slowly (0.03 ml / min) injecting into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 20 minutes;
[0084] 4) dissolving 0.25 mmol of selenium powder in 0.25 ml of trioctylphosphine and 0.1 mmol of cadmium acetate in 1 ml of oleic acid, then mixing the two and slowly (0.05 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 20 minutes;
[0085] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0086] 6) Cooling the solution in 5) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0087] Example 3
[0088] This embodiment provides a quantum dot and a preparation method thereof. The difference between the quantum dot 100 of this embodiment and the quantum dot 100 of embodiment 1 is that the materials of the core 110, the first inner shell 121, the second inner shell 122 and the outer shell 130 are Zn 0.2 Cd 0.8 S / ZnSeS / ZnCdSe / ZnS. The diameter of the quantum dot 100 of this embodiment is 12.7 nm, the diameter of the core 110 is 3.1 nm, and the thicknesses of the first inner shell 121, the second inner shell 122 and the outer shell 130 are 2.1 nm, 1.5 nm and 1.2 nm respectively.
[0089] The steps for preparing the quantum dots in this embodiment are as follows:
[0090] 1) Add 3 mmol of zinc acetate, 0.9 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0091] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 15 minutes to obtain a quantum dot core solution;
[0092] 3) dissolving 0.25 mmol sulfur powder and 0.25 mmol selenium powder in 0.5 ml trioctylphosphine, and then slowly (0.03 ml / min) injecting into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 20 minutes;
[0093] 4) dissolving 0.25 mmol of selenium powder in 0.25 ml of trioctylphosphine and 0.1 mmol of cadmium acetate in 1 ml of oleic acid, then mixing the two and slowly (0.05 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 20 minutes;
[0094] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0095] 6) Cooling the solution in 5) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0096] Example 4
[0097] This embodiment provides a quantum dot and a preparation method thereof. The difference between the quantum dot 100 of this embodiment and the quantum dot 100 of embodiment 1 is that the materials of the core 110, the first inner shell 121, the second inner shell 122 and the outer shell 130 are Zn 0.2 Cd 0.8 S / Zn 0.8 Cd 0.2 S / ZnCdSe / ZnS. The diameter of the quantum dot 100 of this embodiment is 12.7 nm, the diameter of the core 110 is 3.1 nm, and the thicknesses of the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are 2.1 nm, 1.5 nm and 1.2 nm respectively.
[0098] The steps for preparing the quantum dots in this embodiment are as follows:
[0099] 1) Add 3 mmol of zinc acetate, 0.9 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0100] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 25 minutes to obtain a quantum dot core solution;
[0101] 3) dissolving 0.5 mmol sulfur powder in 0.5 ml trioctylphosphine and 0.15 mmol cadmium acetate in 1.5 ml oleic acid, then mixing the two and slowly (0.07 ml / min) injecting them into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 30 minutes;
[0102] 4) dissolving 0.25 mmol of selenium powder in 0.25 ml of trioctylphosphine and 0.1 mmol of cadmium acetate in 1 ml of oleic acid, then mixing the two and slowly (0.05 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 20 minutes;
[0103] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0104] 6) Cooling the solution in 5) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0105] Example 5
[0106] This embodiment provides a quantum dot and a preparation method thereof. The difference between the quantum dot 100 of this embodiment and the quantum dot of embodiment 2 is that x is 0.6. The diameter of the quantum dot 100 of this embodiment is 15.3 nm, the diameter of the core 110 is 5.7 nm, and the thicknesses of the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are 2.1 nm, 1.5 nm and 1.2 nm, respectively.
[0107] The steps for preparing the quantum dots in this embodiment are as follows:
[0108] 1) Add 3 mmol of zinc acetate, 0.5 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0109] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 20 minutes to obtain a quantum dot core solution;
[0110] 3) dissolving 0.25 mmol sulfur powder and 0.25 mmol selenium powder in 0.5 ml trioctylphosphine, and then slowly (0.03 ml / min) injecting into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 20 minutes;
[0111] 4) dissolving 0.25 mmol of selenium powder in 0.25 ml of trioctylphosphine and 0.1 mmol of cadmium acetate in 1 ml of oleic acid, then mixing the two and slowly (0.05 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 20 minutes;
[0112] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0113] 6) Cooling the solution in 5) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0114] Example 6
[0115] This embodiment provides a quantum dot and a preparation method thereof. The difference between the quantum dot 100 of this embodiment and the quantum dot of embodiment 2 is that x is 0.7. The diameter of the quantum dot 100 of this embodiment is 16.1 nm, the diameter of the core 110 is 6.5 nm, and the thicknesses of the first inner shell layer 121, the second inner shell layer 122 and the outer shell layer 130 are 2.1 nm, 1.5 nm and 1.2 nm, respectively.
[0116] The steps for preparing the quantum dots in this embodiment are as follows:
[0117] 1) Add 3.5 mmol of zinc acetate, 0.4 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0118] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 20 minutes to obtain a quantum dot core solution;
[0119] 3) dissolving 0.25 mmol sulfur powder and 0.25 mmol selenium powder in 0.5 ml trioctylphosphine, and then slowly (0.03 ml / min) injecting into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 20 minutes;
[0120] 4) dissolving 0.25 mmol of selenium powder in 0.25 ml of trioctylphosphine and 0.1 mmol of cadmium acetate in 1 ml of oleic acid, then mixing the two and slowly (0.05 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 20 minutes;
[0121] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0122] 6) Cooling the solution in 5) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0123] Example 7
[0124] The structure of the quantum dot 200 of this embodiment is as follows Figure 2 As shown, it includes an inner core 210, two groups of inner shell units 220 and an outer shell 230 sequentially coated on the surface of the inner core 210, and each group of inner shell units 220 includes a first inner shell 221 and a second inner shell 222. The materials of the inner core 210, the first inner shell 221, the second inner shell 222, the first inner shell 221, the second inner shell 222 and the outer shell 230 from the inner core 210 to the outer shell 230 are Zn 0.5 Cd 0.5 S / Zn 0.8 Cd 0.2 S / Zn 0.6 Cd 0.4 S / Zn 0.8 Cd 0.2 S / Zn 0.6 Cd 0.4 S / ZnS, the diameter of the quantum dot 200 in this embodiment is 14.6nm, the diameter of the core 210 is 5nm, the thickness of the first inner shell 221 is 1.05nm, the thickness of the second inner shell is 0.75nm, the thickness of the first inner shell 221 is 1.05nm, the thickness of the second inner shell 222 is 0.75nm, and the thickness of the outer shell 230 is 1.2nm.
[0125] The steps for preparing the quantum dots in this embodiment are as follows:
[0126] 1) Add 6 mmol of zinc acetate, 0.6 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0127] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 25 minutes to obtain a quantum dot core solution;
[0128] 3) dissolving 0.25 mmol sulfur powder in 0.25 ml trioctylphosphine and 0.07 mmol cadmium acetate in 0.7 ml oleic acid, then mixing the two and slowly (0.04 ml / min) injecting them into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 15 minutes;
[0129] 4) dissolving 0.12 mmol sulfur powder in 0.15 ml trioctylphosphine and 0.05 mmol cadmium acetate in 0.5 ml oleic acid, then mixing the two and slowly (0.04 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 10 minutes;
[0130] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0131] 6) Dissolve 0.12 mmol sulfur powder in 0.15 ml trioctylphosphine and 0.05 mmol cadmium acetate in 0.5 ml oleic acid, then mix the two and slowly (0.04 ml / min) inject them into the solution in 3) to grow the second inner shell layer, and react for 10 minutes;
[0132] 7) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, and then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0133] 8) Cooling the solution in 7) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0134] Embodiment 8 to Embodiment 14
[0135] The quantum dots of Examples 1 to 7 are respectively used to produce QLEDs of Examples 8 to 14, and the steps are as follows:
[0136] 1) Cleaning the patterned ITO glass substrate, drying and UVO treatment;
[0137] 2) PEDOT:PSS was deposited as HIL on ITO substrate using solution method with a thickness of 40 nm;
[0138] 3) Depositing TFB as HTL on HIL by solution method with a thickness of 30 nm;
[0139] 4) Depositing the quantum dot solutions of Examples 1 to 7 as EML on the HTL by a solution method, with a thickness of 40 nm;
[0140] 5) Mg-doped ZnO nanoparticles were deposited on the EML using a solution method as an ETL with a thickness of 50 nm;
[0141] 6) Ag was deposited on the ETL as a cathode using an evaporation method with a thickness of 100 nm.
[0142] Comparative Example 1
[0143] This comparative example is a comparative example of Example 1, and provides a quantum dot and a preparation method thereof. The difference between this comparative example and the quantum dot of Example 1 is that the material of the core is Zn 0.2 Cd 0.8 S, the diameter of the core is 2.5nm, and the diameter of the quantum dot is 12.1nm.
[0144] The preparation steps of the quantum dots in this comparative example are as follows:
[0145] 1) Add 3 mmol of zinc acetate, 0.9 mmol of cadmium acetate and 10 ml of oleic acid into a 100 ml three-necked flask, introduce nitrogen, heat to 180°C and stir until the solution is clear and transparent, then add 20 ml of octadecene and heat to 320°C;
[0146] 2) dissolving 1 mmol of sulfur powder in 1 ml of trioctylphosphine, and then rapidly injecting it into the solution in 1), and reacting for 15 minutes to obtain a quantum dot core solution;
[0147] 3) dissolving 0.5 mmol sulfur powder in 0.5 ml trioctylphosphine and 0.15 mmol cadmium acetate in 1.5 ml oleic acid, then mixing the two and slowly (0.07 ml / min) injecting them into the quantum dot core solution in 2) to grow the first inner shell layer, and reacting for 30 minutes;
[0148] 4) dissolving 0.25 mmol sulfur powder in 0.25 ml trioctylphosphine and 0.1 mmol cadmium acetate in 1 ml oleic acid, then mixing the two and slowly (0.05 ml / min) injecting them into the solution in 3) to grow the second inner shell layer, and reacting for 20 minutes;
[0149] 5) Dissolve 0.2 mmol sulfur powder in 0.2 ml trioctylphosphine, then slowly (0.02 ml / min) inject it into the solution in 4) to grow the outer shell layer, and react for 10 minutes;
[0150] 6) Cooling the solution in 5) to room temperature, adding excess acetone to precipitate quantum dots, then removing the acetone and adding n-octane to dissolve to obtain a quantum dot solution, and repeating this process 3 times to obtain a pure quantum dot solution.
[0151] Comparative Example 2
[0152] The quantum dots of comparative example 1 are used to produce the QLED of comparative example 2, and the steps are as follows:
[0153] 1) Cleaning the patterned ITO glass substrate, drying and UVO treatment;
[0154] 2) PEDOT:PSS was deposited as HIL on ITO substrate using solution method with a thickness of 40 nm;
[0155] 3) Depositing TFB as HTL on HIL by solution method with a thickness of 30 nm;
[0156] 4) Depositing the quantum dots of Comparative Example 1 on the HTL as EML using a solution method with a thickness of 40 nm;
[0157] 5) Mg-doped ZnO nanoparticles were deposited on the EML using a solution method as an ETL with a thickness of 50 nm;
[0158] 6) Ag was deposited on the ETL as a cathode using an evaporation method with a thickness of 100 nm.
[0159] Performance Test:
[0160] The performance of the QLEDs of Examples 8 to 14 and Comparative Example 2 was tested in the following manner. The test results are shown in Table 1. Figure 5 and Figure 6 shown.
[0161] CE-L curve: obtained by performing IVL (current-voltage-luminance) test on QLED; CE is current efficiency, unit is cd / A; L is luminance, unit is cd / m 2 ;
[0162] LT curve: obtained by testing the life of QLED; L is brightness, T is time; generally, a constant current source is used to input current to the QLED, and the curve of its brightness changing over time is recorded; commonly used life parameters are T 95 , which indicates the time it takes for the brightness of the QLED to decay from the initial value to 95% of the initial value.
[0163] Table 1 Performance test results of QLED of Examples 8 to 14 and Comparative Example 2
[0164] Example / Comparative Example Max.CE(cd / A) <![CDATA[T 95 (h)@50mA / cm 2 ]]> Example 8 11.5 6.7 Example 9 10.6 5.5 Example 10 10.9 3.2 Embodiment 11 10.5 3.5 Example 12 11.2 7.0 Embodiment 13 11.6 6.5 Embodiment 14 9.8 5.8 Comparative Example 2 11.3 1.5
[0165] It can be seen from Table 1 that the efficiency and lifespan of the QLEDs of Examples 8 to 14 are relatively high, indicating that the quantum dot structure of the present invention can enable the electroluminescent device to have high efficiency and lifespan.
[0166] from Figure 5 It can be seen that the efficiency of the QLEDs of Example 8 and Comparative Example 2 is comparable; Figure 6 It can be seen that compared with the QLED of Comparative Example 2, the lifespan of the QLED of Example 8 is significantly increased, indicating that the quantum dot structure of the present invention can effectively improve the device lifespan.
[0167] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0168] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A quantum dot, characterized in that: The quantum dot comprises a core, at least one group of inner shell units and an outer shell layer sequentially coated on the surface of the core; The material of the core is Zn x Cd 1-x S, wherein x is 0 to 1; the size of the core is not less than 3 nm; Each group of the inner shell units comprises a first inner shell and a second inner shell in a direction away from the inner core, wherein the band gap of the first inner shell is larger than the band gap of the inner core and the band gap of the second inner shell; The band gap of the outer shell layer is greater than or equal to the band gap of the first inner shell layer.
2. The quantum dot according to claim 1, characterized in that The size of the core is 3nm to 15nm; and / or The size of the quantum dots is 10 nm to 30 nm; and / or The thickness of the first inner shell layer, the second inner shell layer and the outer shell layer are all 0.35 nm to 3.5 nm.
3. The quantum dot according to claim 1, characterized in that The material of the core is Zn x Cd 1-x S, where x is 0.2 to 0.
7.
4. The quantum dot according to claim 1 or 3, characterized in that: The material of the core is Zn x Cd 1-x S, where x is 0.4 to 0.
6.
5. The quantum dot according to claim 1, characterized in that The material of the first inner shell layer is selected from Zn y Cd 1-y At least one of S and ZnSeS, wherein y is x-1, and x<y<1; The material of the second inner shell layer is selected from Zn z Cd 1-z At least one of S, ZnCdSe and ZnCdSeS, wherein z<y; The material of the outer shell layer is selected from at least one of ZnCdS, ZnSeS and ZnS.
6. The quantum dot according to claim 5, characterized in that The material of the second inner shell layer is Zn z Cd 1-z S, where z ≥ x.
7. The quantum dot according to claim 1, characterized in that The difference between the band gap of the first inner shell layer and the band gap of the core is 0.2eV~1eV, the difference between the band gap of the first inner shell layer and the band gap of the second inner shell layer is 0.1eV~1eV, and the difference between the band gap of the outer shell layer and the band gap of the first inner shell layer is 0.1eV~1eV.
8. The quantum dot according to claim 1, characterized in that The number of groups of the inner shell units is one group; Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.5 Cd 0.5 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S and ZnS; Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.4 Cd 0.6 S, ZnSeS, ZnCdSe and ZnS; Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.2 Cd 0.8 S, ZnSeS, ZnCdSe and ZnS; Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.2 Cd 0.8 S, Zn 0.8 Cd 0.2 S, ZnCdSe and ZnS; Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.6 Cd 0.4 S, ZnSeS, ZnCdSe and ZnS; Preferably, the materials of the core, the first inner shell layer, the second inner shell layer and the outer shell layer are Zn 0.7 Cd 0.3 S, ZnSeS, ZnCdSe and ZnS.
9. The quantum dot according to claim 1, characterized in that The number of groups of the inner shell units is two, and each group of the inner shell units includes a first inner shell and a second inner shell; Preferably, the materials of the inner core, the first inner shell layer, the second inner shell layer, the first inner shell layer, the second inner shell layer and the outer shell layer from the inner core to the outer shell layer are Zn 0.5 Cd 0.5 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S, Zn 0.8 Cd 0.2 S, Zn 0.6 Cd 0.4 S and ZnS.
10. An electroluminescent device, characterized in that: The invention comprises a quantum dot light-emitting layer, wherein the quantum dot light-emitting layer comprises the quantum dots according to any one of claims 1 to 9.